Patriarchal Culture in Film: Between Myth and Meaning (Audience Reception Analysis of The Film“Yuni”) - Budipratiwi, Rizki Ayu; Widuri, Rachma Tri; Citrayomie, Ayoedia Gita (Fakultas Dakwah UIN Saizu Purwokerto, 2023)
Film as an art form is a representation of reality. However, film can also mean reality itself, which is visualized. Film or cinema is embedded in culture and has an exciting relationship with ideology and audience. Thus, films can intervene in human thoughts and feelings. The storyline and film content convey the culture and myths that develop in society. Among the cultural forms that are also part of a film’s narrative is patriarchal culture. Patriarchy is a social system that places men as the main authority figure in social organization. The position of men is higher than that of women in all aspects of social, cultural and economic life. This study aimed to find out the meaning of the audience regarding the patriarchal culture depicted in the film “Yuni”. This research approach is qualitative with the reception analysis method of Stuart Hall’s ‘encoding-decoding’ model. Data collection techniques used focus group discussions (FGD) with five informants. Based on the research results, it can be concluded that the informants are in the opposite position in depicting patriarchal structures in aspects of the patriarchal state, male violence, patriarchal relations and patriarchal culture. They interpret it as a picture of the patriarchal structure still shackles women’s lives.